2015
DOI: 10.1021/ma501916z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Coarse-Grained Ionomer Melts in an External Electric Field

Abstract: We perform molecular dynamics simulations on a set of ionomer melts in the presence of a static, external electric field. We employ the same coarse-grained bead–spring model from our previous simulations, which characterized the zero-field morphologies and dynamics of the isolated or percolated ionic aggregates observed in these systems. Here we investigate the electric field effects on these aggregates. In the linear response regime, the morphology of both isolated and percolated aggregates is unaltered becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 32 publications
2
67
0
Order By: Relevance
“…Ion transport mechanism. Efforts to reveal the ion transport mechanism in ion-containing polymers have been reported both experimentally and computationally [7][8][9][10][31][32][33][34] The consensus from previous studies on how the counterions move in a polymer melt (in the absence of any electric field) is that the counterions have either structural diffusion or vehicular transport. [31][32][33][34] In the former mechanism, the counterions are hopping between oppositely charged monomers, whereas in the latter, the ions diffuse along with their neighbors, that is, an aggregate of counterions and charged monomers moving together.…”
Section: Ionic Clustersmentioning
confidence: 99%
“…Ion transport mechanism. Efforts to reveal the ion transport mechanism in ion-containing polymers have been reported both experimentally and computationally [7][8][9][10][31][32][33][34] The consensus from previous studies on how the counterions move in a polymer melt (in the absence of any electric field) is that the counterions have either structural diffusion or vehicular transport. [31][32][33][34] In the former mechanism, the counterions are hopping between oppositely charged monomers, whereas in the latter, the ions diffuse along with their neighbors, that is, an aggregate of counterions and charged monomers moving together.…”
Section: Ionic Clustersmentioning
confidence: 99%
“…The influences of the counterions on the polyelectrolyte dynamics are certainly nontrivial, at the length scales of the monomers and of the sub-chains. 40,41 Webb and coworkers showed that the dynamics of a single negatively charged polyelectrolyte is substantially suppressed across multiple length scales for different concentrations of lithium cations compared to that of neat polymers. 41 Here we also characterize the dynamics of the confined polyelectrolyte at different length scales through the relaxation time of its Rouse modes.…”
Section: Relaxation Time Of the Rouse Modes Of The Polyelectrolytementioning
confidence: 99%
“…Sethuraman et al has observed that five different ion transport mechanisms in lamellar BCPs and homopolymers (HPs), and that the mean square displacement of BCPs decreases with increasing charge ratio [25]. Ting et al found that the ion transport of ionomer melt displays a different regime influenced by the strength of electric field and the ionic aggregate morphology [26]. However, there exist relatively few studies that attempt to understand the mechanical properties of the charged BCPs.…”
Section: Introductionmentioning
confidence: 99%